Pregnancies in Women with a Previous Complete Uterine Rupture - Iqbal Al-Zirqi; Siri Vangen (Hindawi Limited, 2023)
Objective. To study the outcomes of new pregnancies after a previous complete uterine rupture. Design. Descriptive study based on population data from the Medical Birth Registry of Norway, the Patient Administration System, and the medical records. Sample. Maternities with a previous complete uterine rupture in Norway during the period 1967-2011 (N = 72), extracted from 2 455 797 maternities. Method. We measured the rate of new complete ruptures and partial ruptures, as well as the maternal and perinatal outcomes of these pregnancies. The characteristics of both previous ruptures and new ruptures were described. Results. Among 72 maternities, there were thirty-seven with previous ruptures in the lower segment (LS) and 35 outside the LS. We found three new complete ruptures and six uneventful partial ruptures, resulting in a rate of 4.2% and 8.3%, respectively. All three complete ruptures occurred preterm in scars outside the LS. The rate of the new complete rupture was 0% in those with previous ruptures in the LS and 8.6% in those with previous ruptures outside the LS. The corrected perinatal mortality was 1.3%, and prematurity (<37 weeks) was high (36.1%); this was noticed even in the absence of new ruptures and was mostly iatrogenic. Two hysterectomies were performed in the absence of rupture and two cases had abnormal invasive placenta. Conclusion. The prognosis for pregnancies after a previous complete uterine rupture is favorable. Prematurity is a problem caused by both obstetrician and mother's anxiety; therefore, the timing of delivery is the most challenging. Management should include careful counseling, vigilance for symptoms, and immediate delivery when a rupture is suspected.